Herlyn-Werner-Wunderlich: A Rare Disease - Yoki Citra Perwira; Jeffy Winarya Wahyudi (MEDICINUS, 2023)
Herlyn-Werner-Wunderlich (HWW) is a rare Mullerian disorder characterized by uterine didelphys, hemivaginal obstruction, and ipsilateral renal agenesis. This paper aimed to describe a rare case of HWW in order to give better understanding of the disease, as well as diagnosis and treatment. Then urgent action is taken in the form of incision and drainage of pus. Methods: We searched medical record of a 17-year-old girl complaining of vaginal pain since menarche. Ultrasound examination found hematocolpos and vaginal septum, pelvic MRI found uterus didelphys and left renal agenesis, then the septal incision was performed to facilitate pus drainage. Conclusion: Herlyn-Werner-Wunderlich is a rare condition with varying age of onset. Anamnesis, physical examination, ultrasonography, and MRI are needed to confirm diagnosis. As an urgent measure, a septal incision and pus drainage are performed to reduce symptoms and complications that could occur in the future. In addition, the patient needs to undergo septal resection as a follow-up treatment which can only be done in a hospital where urogenital and reconstruction divisions are available.